Value Co-Creation pada Bisnis Syariah Konstruksi Oil dan Gas di Indonesia - Sukma Nugraha (Entrepreneurship Faculty, Universitas Garut, 2020)
Abstract- Progress in terms of technology and information now has given rise to new trends in the economic field. In supporting a company's business performance, the term value co-creation creation is known. The research method used is descriptive survey and explanatory survey methods with organizational analysis units. The results of this study are the development of other variables that affect customer trust and repurchase intention and questioners will be distributed to related industries that have the same population as PT. Mutiara Global Industry as a company in the field of oil and gas and steel construction. Abstrak– Kemajuan segi teknologi dan informasi saat ini telah melahirkan kecenderungan baru dalam bidang ekonomi. Dalam mendukung kinerja bisnis suatu perusahaan, dikenal istilah value co-creation creation. Metode penelitian yang digunakan adalah metode descriptive survey dan explanatory survey dengan unit analisis organisasi. Hasil dari penelitian ini adalah adanya pengembangan terhadap variable –variable lainnya yang mempengaruhi terhadap kepercayaan customer dan repurchase intention dan questioner akan di sebar ke industry terkait yang memiliki populasi yang sama dengan PT. Mutiara Global Industry sebagai perusahaan di bidang oil and gas dan konstruksi baja.